The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1530/eje.0.1400341
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effect of insulin via nitric oxide production in the Zucker diabetic fatty rat, an animal model for non-insulin-dependent diabetes mellitus

Abstract: It has been reported that insulin treatment improves hypertension in patients with diabetes mellitus. The mechanisms of the antihypertensive effect of insulin, however, remain to be fully elucidated. In the present study, we investigated a possible involvement of nitric oxide (NO) in insulin-induced reduction of blood pressure using the Zucker diabetic fatty (ZDF) rat, an animal model of non-insulin-dependent diabetes mellitus. The animals were divided into three groups and treated for 4 weeks with daily subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
(48 reference statements)
2
11
0
Order By: Relevance
“…Insulin-induced NOS-like immunostaining in the arteries supported our previous observation that insulin-treatment induced NOS in aorta of ZDF rats as studied by NADPH diaphorase staining (2). The present data indicate that improvement of hypertension by insulin treatment was due to induction of NOS in the arteries in ZDF rats.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Insulin-induced NOS-like immunostaining in the arteries supported our previous observation that insulin-treatment induced NOS in aorta of ZDF rats as studied by NADPH diaphorase staining (2). The present data indicate that improvement of hypertension by insulin treatment was due to induction of NOS in the arteries in ZDF rats.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that serum levels of NO metabolites were increased by insulin treatment in the ZDF rat (1,2). Furthermore, NO synthase (NOS) activity and NADPH diaphorase staining were enhanced by insulin treatment (2). These data suggest that insulin treatment induces NOS in the ZDF rat.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Therefore, poor glycemic control is considered to induce hypertension in diabetes mellitus [2,8]. Also, in ZDF rats, insulin reduced the blood pressure [13]. Moreover, an antihyperglycemic effect in male GK rats caused a pronounced suppression of both the systolic and the diastolic blood pressure [12].…”
Section: =03134 P=003)mentioning
confidence: 99%